Regionalizing indicators for marine ecosystems: Bering Sea–Aleutian Island seabirds, climate, and competitors. (July 2017) - Sydeman, William J.; Thompson, Sarah Ann; Piatt, John F.; García-Reyes, Marisol; Zador, Stephani; Williams, Jeff C.; Romano, Marc; Renner, Heather M.
Highlights: Seabird phenology and breeding success were combined as multivariate indicators. Four modes of variability suggest seabird indicators respond to different forcings. Kittiwakes and murres responded differently to ocean climate and competitor forcing. Caution is needed when constructing ecosystem-wide indicators from seabirds. Abstract: Seabirds are thought to be reliable, real-time indicators of forage fish availability and the climatic and biotic factors affecting pelagic food webs in marine ecosystems. In this study, we tested the hypothesis that temporal trends and interannual variability in seabird indicators reflect simultaneously occurring bottom-up (climatic) and competitor (pink salmon) forcing of food webs. To test this hypothesis, we derived multivariate seabird indicators for the Bering Sea–Aleutian Island (BSAI) ecosystem and related them to physical and biological conditions known to affect pelagic food webs in the ecosystem. We examined covariance in the breeding biology of congeneric pelagic gulls (kittiwakes Rissa tridactyla and R. brevirostris ) and auks (murres Uria aalge and U. lomvia ), all of which are abundant and well-studied in the BSAI. At the large ecosystem scale, kittiwake and murre breeding success and phenology (hatch dates) covaried among congeners, so data could be combined using multivariate techniques, but patterns of response differed substantially between the genera. While data from all sites ( n  = 5) in the ecosystem could be combined, the south eastern Bering Sea shelf colonies (St. George, St. Paul, and Cape Peirce) provided the strongest loadings on indicators, and hence had the strongest influence on modes of variability. The kittiwake breeding success mode of variability, dominated by biennial variation, was significantly related to both climatic factors and potential competitor interactions. The murre indicator mode was interannual and only weakly related to the climatic factors measured. The kittiwake phenology indicator mode of variability showed multi-year periods ("stanzas") of late or early breeding, while the murre phenology indicator showed a trend towards earlier timing. Ocean climate relationships with the kittiwake breeding success indicator suggest that early-season (winter–spring) environmental conditions and the abundance of pink salmon affect the pelagic food webs that support these seabirds in the BSAI ecosystem.